ANALISIS KERUSAKAN POROS BRINE INJECTION PUMP - Kartikasari, Ratna; -, Antony (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
PT. Geo Dipa Energy Dieng unit is one form of industry exploiting geothermal steam(vapor) that uses abrine injection pump. Brine injection pump is a pump for injecting brine into injection wells. Pump using the VC type is the type of pump that has suction and discharge nozzle shead. The problems that always arise in the operation of the brine injection pump shaft is break age of component smade ​​of stainless steel SS420 in are latively short time. This study aims to determine the cause of brine injection pump shaft break age in avery short time.Stages of an alysis performe distesting the chemical composition using spectrometry and EDAX, macrophotoonfracturesurfaces, and microphoto on the area closest to the fracture surface using The results showed that the initial damage occurs precisely in the initial crack. Further more,the crack propagation occurs according to the loading pattern until the ductilet earing occurs before fracture. Generally, the pattern of fracture indicate sinter-crystalline pattern at the beginning of the trans-crystalline cracks and any subsequent stages until fracture occurs. SEMindicate the presence of Cr carbides with elongated patterns that indicatethe cause of fracture. This causes the carbide concentration are as vulnerable tocorrosiveenvironments, so that when the Cl-ions contained in the brine contactaggressively in this area then began collaborating between corrosion and dynamic load causes the initial crack and followed bycrack propagation that very fast into the brittle fracture pattern.